The role of physiotherapy in the treatment of men’s sexual dysfunction (erectile dysfunction and premature ejaculation): a review - Mohammad Roostayi; Nooshin Rahdar (Physiotherapy Quarterly, 2022)
Sexual dysfunction in men is one of the issues that has an effect on the mental status, couples’ relationships, and their quality of life. In addition to the psychological and emotional disturbances that sexual dysfunction can cause, some physical attributes that induce problems are reduced joint mobility, changes in the tone and lack of control and rhythm of pelvic floor muscles, presence of trigger points in the pelvic area, reduced blood flow and pain in the genital area. Previous research has shown that, apart from the importance of psychological intervention, physical therapy, such as manual therapies, pelvic floor muscle tone regulation, performing specific aerobic exercises, raising the awareness of the patient, posture correction, improving mobility, and reducing pain, can have a significant impact on improving sexual function and quality of life in men. The purpose of this article is to introduce the role of physiotherapy in alleviating men’s sexual dysfunction.